12.2k views
3 votes
Solve this equation. Enter your answer in the box.
13(y+7)=3(y−1).

User Daniel Tam
by
4.8k points

2 Answers

0 votes

Answer


\red{13(y + 7) = 3(y - 1)} \\ \\ \color{red}\dashrightarrow \: 13y + 91 = 3y - 3 \\ \\ \color{pink} \dashrightarrow \: 13y - 3y = - 3 - 91 \\ \\ \pink{ \dashrightarrow \: 10y = - 94} \\ \\ \purple{ \dashrightarrow \: y = \frac{ \cancel{- 94} {}^( - 47) }{ \cancel{10} {}^(5) } }\\ \\ \green{ \dashrightarrow \: y = ( - 47)/(5) }

Hence, The Answer is


=( - 47)/(5)

User Sjwdavies
by
5.0k points
3 votes

★To Solve :


\rm\blue{13(y+7) = 3(y-1)}

⠀⠀⠀⠀⠀

★SOLUTION :


\rm\red\leadsto{13(y+7) = 3(y-1)}


\rm\red\leadsto{13*{y}+13*7= 3*{y}-3*1}


\rm\red\leadsto{13y+91=3y-3}


\rm\red\leadsto{13y-3y=-3-91}


\rm\red\leadsto{10y=-94}


\rm\red\leadsto{} y =\frac{ { \cancel{-94}}^( \:-45 ) }{ { \cancel{10}}^( \: 5) }


\rm\red\leadsto{y=}(-47)/(5)

____________________

User JWood
by
5.1k points